Effectiveness of popular race walking drills in activating key muscles - Hanley, B.; Drake, A. (New Studies in Athletics, 2016)
Race walking is a technical event where coaches frequently use event-specific drills to develop their athletes' strength and movement skills in training. The purpose of this study was to measure the effectiveness of six drills often used by race walkers because of their value in activating key muscles. The muscle activity of eight lower limb muscles was measured using electromyography In 10 young race walkers as they completed the six drills down a biomechanics runway. Two force plates were used to measure contact times and flight times, and the results were compared to the muscle activity recorded during normal (competition-paced) race walking. In general, the drills chosen for analysis achieved greater activation of the key muscles of the gluteus maximus, rectus femoris and vastus lateralis; however, they were not as beneficial with regard to the activity of biceps femoris and tibialis anterior, two muscles that are often injured in race walking. Coaches are advised to ensure that drills used in training are specific to their athletes' needs and do not inadvertently lead to non-legal technique (e.g., through increased flight time).